2010
DOI: 10.1007/s11230-010-9252-0
|View full text |Cite
|
Sign up to set email alerts
|

A new tetraphyllidean genus and species, Caulopatera pagei n. g., n. sp. (Tetraphyllidea: Phyllobothriidae), from the grey carpetshark Chiloscyllium punctatum Müller & Henle (Orectolobiformes: Hemiscylliidae)

Abstract: A new genus and species of tetraphyllidean cestode, Caulopatera pagei n. g., n. sp., is described from the grey carpetshark Chiloscyllium punctatum Müller & Henle in Moreton Bay, Australia. The new genus is placed in the Phyllobothriidae, subfamily Phyllobothriinae. Caulopatera n. g. is distinct from all other phyllobothriine genera in having stalked, circular, non-loculate bothridia that lack an apical sucker, testes that are restricted to the region anterior to the cirrus-sac and circum-medullary vitelline f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The tree resulting from the analysis indicates that Ambitalveolus is the earliest diverging lineage of Clade 3. The grouping of Caulopatera and Carpobothrium as sister taxa supports the hypothesis advanced by Cutmore et al (2010), and later endorsed by Caira et al (2017) when establishing Clade 3, that these genera are close relatives. Within Carpobothrium, the earliest diverging species is Carpobothrium megaphallum from Chiloscyllium griseum.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The tree resulting from the analysis indicates that Ambitalveolus is the earliest diverging lineage of Clade 3. The grouping of Caulopatera and Carpobothrium as sister taxa supports the hypothesis advanced by Cutmore et al (2010), and later endorsed by Caira et al (2017) when establishing Clade 3, that these genera are close relatives. Within Carpobothrium, the earliest diverging species is Carpobothrium megaphallum from Chiloscyllium griseum.…”
Section: Discussionsupporting
confidence: 74%
“…Of the seven species of Chiloscyllium examined for cestodes to date (see Caira et al 2021b), this genus has only ever been reported from the undescribed species Chiloscyllium cf. punctatum in Moreton Bay, Australia (Cutmore et al 2010). Nonetheless, in the absence of other data, the species of Chiloscyllium that have not yet been examined for cestodes would seem to be the most viable candidates as hosts for other species of Caulopatera.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations